If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.2 = 3sinx + 1 Reorder the terms: 1.2 = 1 + 3insx Solving 1.2 = 1 + 3insx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-3insx' to each side of the equation. 1.2 + -3insx = 1 + 3insx + -3insx Combine like terms: 3insx + -3insx = 0 1.2 + -3insx = 1 + 0 1.2 + -3insx = 1 Add '-1.2' to each side of the equation. 1.2 + -1.2 + -3insx = 1 + -1.2 Combine like terms: 1.2 + -1.2 = 0.0 0.0 + -3insx = 1 + -1.2 -3insx = 1 + -1.2 Combine like terms: 1 + -1.2 = -0.2 -3insx = -0.2 Divide each side by '-3nsx'. i = 0.06666666667n-1s-1x-1 Simplifying i = 0.06666666667n-1s-1x-1
| 65x=130 | | 3/8x-y=-2 | | 8x+6y=11 | | 8x-6y=84 | | 2(2x-(4-7y+6x)+5y)= | | h^2+6h-23=0 | | 3x+15=45+x | | 20x+30=180 | | (3x-4x+2y)*(2y+3y+2x)= | | -2x-5(x+1)=-x | | 6e^3x=30 | | 11[5-(4-2x)]+10x=4(8x+4)-5 | | w(26)=3x-1 | | xFactor+3x+2=0 | | y=.5x+-19 | | 5x-36=34+4x | | 5x+4(x-2)=10x+6 | | -2x+5x-14=3(x-1)-26 | | 1.2(b-12)=84 | | g=8y-m/y | | -x-2=-3x-5 | | 0.6x+14.8=x-1.56 | | 331.11=9(0.08m+26.90+0.10(26.90)) | | x^3-1/4x^2-2x-3=0 | | 6x+6.4=2(4x-2.8) | | 245=70+t | | 3(2x+7)=5x+17+x | | 2q+457=875 | | [(x-10)-24]+(x-10)+x=180 | | 8x+3-10=-2(x-2)+3 | | -3(t-2)+8t=7t-4 | | 4t+13b=487 |